PENERAPAN MODEL PEMBELAJARAN INKUIRI PADA MATERI RUANG LINGKUP BIOLOGI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SMA NEGERI 1 MUTIARA - Makawiyah, Makawiyah; Zuraida, Zuraida; Salbiah, Salbiah (Jurnal Sains Riset, 2024)
Research with the title Application of the Inquiry Learning Model in Biology Scope Material to Improve Learners Learning Outcomes at SMA Negeri 1 Mutiara. This research aims to determine the improvement in learners' learning outcomes through the application of the inquiry learning model to biology scope material at SMA Negeri 1 Mutiara. The population is all learners of class X MIPA SMA N 1 Mutiara consisting of 6 classes with a total of 180 learners. Of the six classes by using a random sampling technique (random method) to determine the experimental class and control class. The data collection technique for this research is a test technique in the form of 25 multiple-choice questions. From the results of data analysis, it was obtained that tcountttable was 4.511.67 at a significance level of 0.05. Based on these data, the hypothesis formulated, namely that the application of the Inkuri learning model can increase learners ' understanding of learning concepts in biology scope material in class X SMA N 1 Mutiara, can be accepted as true.Keywords : Inquiry Learning Model, Learning Outcomes, Scope of Biology